Room temperature deposited highly conductive HfNx films for high-performance HfN/Si junction diodes - Khan, Amir Sohail; Iqbal, Shahid; Duy, Le Thai; Kumar, Ashish; Khan, Muhammad Waqas; Kumar, Mohit; Seo, Hyungtak (Surfaces and Interfaces, 2024)
Transition metal nitrides are valuable materials for many technological applications due to their favorable physical characteristics, including conductivity, high temperature stability, and hardness. Among them, hafnium nitride (HfN) thin films of high attributes are crucial for semiconductor applications. However, achieving performance efficiency of HfN films with desired electrical performance via conventional deposition methods is a challenging task. Herein, we have achieved room temperature growth of highly oriented cubic HfN thin film grown on Si substrate by process optimization of radio frequency (RF) magnetron sputtering. HfN thin films were structurally, morphologically, and electrically characterized. The metallic behavior of HfN films was confirmed through current-voltage measurements; it showcased excellent electrical conductivity, signifying low resistivity (≈ 0.55 kΩ sq-1), revealing promising evidence for its potential practical application. Moreover, the first-principles calculations were also conducted to gain further insights into the electrical performance of the HfN films. These findings lay a solid foundation for further exploration and development of HfN-based junction diodes, as the observed characteristics offer significant potential for enhancing device performance in various electronic domains.
Keywords: DFT analysis; HfNx metallic films; High conductivity; Junction diode; RF sputtering; Transition metal nitrides